2(m+3)+1=23

Simple and best practice solution for 2(m+3)+1=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(m+3)+1=23 equation:


Simplifying
2(m + 3) + 1 = 23

Reorder the terms:
2(3 + m) + 1 = 23
(3 * 2 + m * 2) + 1 = 23
(6 + 2m) + 1 = 23

Reorder the terms:
6 + 1 + 2m = 23

Combine like terms: 6 + 1 = 7
7 + 2m = 23

Solving
7 + 2m = 23

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 2m = 23 + -7

Combine like terms: 7 + -7 = 0
0 + 2m = 23 + -7
2m = 23 + -7

Combine like terms: 23 + -7 = 16
2m = 16

Divide each side by '2'.
m = 8

Simplifying
m = 8

See similar equations:

| 5x-10x+14=-3x+6 | | 3+y/4=1.95 | | 2t+38=5(t+1) | | x+4+6x-6=180 | | 23x-8-14x=21 | | x+5+x=10 | | -2(x-4)=-16 | | x+4=6x-6 | | 0=3x-9-4x | | 5x+-3=-18 | | 14+8a=4a-10 | | X+3y=60 | | 7c+28=105 | | 16x-9x-15=13 | | 4c-13c-6c=-49 | | 35x^2y^2+9xy+-2=0 | | 2(6w-9)-6=24-12w | | 5x-2=15x+112 | | 5-2z=17 | | 15r+6s-11t+r-9s+t-2s+5r-2t-r= | | 4+x+7=-36 | | 28-0.3y=0.7t-12 | | x=16+3y | | 35(x^2)*(y^2)+9xy-2=0 | | x^4-9x^3+18x^3=0 | | x+4+7=-36 | | 5a-4(3a+7)=-221 | | 9(x-4)=-3x+96 | | 3p-12=12+15p | | 10-(-25)=d | | 10w-3=8w | | 6d-4=2(5d-2) |

Equations solver categories